Efficacy of computed tomography in diagnosing pulmonary hypertension: A systematic review and meta-analysis - Chen, Riken; Liao, Huizhao; Deng, Zhenan; He, Zhenfeng; Zheng, Zhenzhen; Lu, Jianmin; Jiang, Mei; Wu, Xiaofeng; Guo, Wenliang; Huang, Zijie; Chen, Huimin; Hong, Cheng; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective This study seeks to evaluate the diagnostic value of computed tomography (CT) in pulmonary hypertension. Method PubMed, Embase, Scopus, and Web of Science databases were searched to obtain the relevant English literature, and the retrieval time until June 2022. The quality of the included studies is evaluated using the QUADAS-2 tool. The quality of the included studies was assessed, followed by a meta-analysis, analyze heterogeneity, summarize sensitivity and specificity, draw the comprehensive subject working characteristics (sROC) curve, calculate the area under the curve and conduct subgroup analysis and sensitivity analysis to find the source of the heterogeneity. Results A total of 12 articles were included, all with pulmonary artery diameter/liter aortic diameter >1 or 1 as the diagnostic criteria for pulmonary hypertension, and a total of 1,959 patients were included. Deek’s funnel plot analysis suggests that there is no significant publication bias (P = 0.102). The combined sensitivity was 0.652 (95% CI: 0.579, 0.719), combined specificity was 0.830 (95% CI: 0.796, 0.880), positive likelihood ratio was 3.837 (95% CI: 3.215, 4.579), negative likelihood ratio was 0.419 (95% CI: 0.346, 0.507), diagnostic odds ratio was 9.157 (95% CI: 6.748, 12.427) and area under the summary receiver operating characteristic (SROC) curve was 0.84 (95% CI: 0.81, 0.87). Conclusion The CT examination of pulmonary artery diameter/aortic artery hypertension is worthy of clinical application.